2008
DOI: 10.2337/db07-0993
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of AMP-Activated Protein Kinase Protects Pancreatic β-Cells From Cytokine-Mediated Apoptosis and CD8+ T-Cell–Induced Cytotoxicity

Abstract: Objective Apoptotic destruction of insulin-producing pancreatic β-cells is involved in the aetiology of both type 1 and type 2 diabetes. AMP-activated protein kinase (AMPK) is a sensor of cellular energy charge whose sustained activation has recently been implicated in pancreatic β-cell apoptosis and in islet cell death post-transplantation. Here, we examine the importance of β-cell AMPK in cytokine-induced apoptosis and in the cytotoxic action of CD8+ T cells. Research Design and Methods Clonal MIN6 β-cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 54 publications
(33 reference statements)
7
41
0
1
Order By: Relevance
“…According to this proposal, treatment with AICAR prevented hyperinsulinemia and preserved b-cell mass in fat Zucker rats (Pold et al 2005). In contrast, it was also demonstrated that AICAR activation of AMPK in isolated b-cells increased apoptosis (Kefas et al 2003), whereas AMPK inhibition protected b-cell toxicity and apoptosis (Riboulet-Chavey et al 2008). Based on our data and on the aforementioned evidence, one can assume that overall exercise-induced AMPK activation would protect b-cells by counteracting elevated blood nutrient glucolipotoxicity-induced damage as well as by reducing GIIS-associated stress, rather than enhancing intrinsic b-cell survival pathways.…”
Section: Discussionmentioning
confidence: 99%
“…According to this proposal, treatment with AICAR prevented hyperinsulinemia and preserved b-cell mass in fat Zucker rats (Pold et al 2005). In contrast, it was also demonstrated that AICAR activation of AMPK in isolated b-cells increased apoptosis (Kefas et al 2003), whereas AMPK inhibition protected b-cell toxicity and apoptosis (Riboulet-Chavey et al 2008). Based on our data and on the aforementioned evidence, one can assume that overall exercise-induced AMPK activation would protect b-cells by counteracting elevated blood nutrient glucolipotoxicity-induced damage as well as by reducing GIIS-associated stress, rather than enhancing intrinsic b-cell survival pathways.…”
Section: Discussionmentioning
confidence: 99%
“…15 Cytokines are also known to stimulate AMPK activity in b-cells, 26 but the mechanisms underlying this activation remained unclear. Here we show that AMPK activation requires the production of NO, and can be achieved with thapsigargin but not with tunicamycin, suggesting that the depletion of ER Ca 2 þ and the subsequent increase in cytosolic Ca 2 þ concentration, rather than the ER stress per se, trigger the activation of the kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Although AMPK activation may initially promote cell survival by enhancing ATP generation, this study demonstrates that prolonged AMPK activation during DN-HNF1A induction or pharmacological activation of AMPK with AICAR induces INS-1 cell apoptosis. Indeed, previous studies have demonstrated that prolonged activation of AMPK results in beta cell apoptosis in insulinoma cells (23) and in isolated islets (35). Moreover, transplantation of islets expressing a constitutively active form of AMPK to streptozotocin-induced diabetic mice resulted in a reduced level of beta cell survival compared with control syngeneic islets, whereas those expressing a dominant- negative form of AMPK improved graft efficiency (34).…”
Section: Discussionmentioning
confidence: 99%